The importance of competition for light depends on productivity and disturbance. Issue 22 (26th October 2018) - Hautier, Yann; Vojtech, Eva; Hector, Andy
Abstract: Eutrophication is a major cause of biodiversity loss. In grasslands, this appears to occur due to asymmetric competition for light following the increases in aboveground biomass production. Here, we report the results of an experiment with five grass species that tests how well‐competitive outcomes can be predicted under a factorial combination of fertilized and disturbed (frequent cutting) conditions. Under fertile conditions, our results confirm earlier success in predicting short‐term competitive outcomes based on light interception in monocultures. This effect was maintained but weakened under less fertile conditions with competition becoming more symmetric. However, under disturbed conditions, competitive outcomes could not be predicted from differences in light interception in monocultures regardless of fertility. Our results support the idea that competition in grasslands shifts from symmetric to asymmetric as fertility increases but that disturbance destroys this relationship, presumably by preventing the development of differences in canopy structure and reducing competition for light. Abstract : Eutrophication is a major cause of biodiversity loss, but the underlying mechanisms are still under intense debate. We show that competition switches from symmetric (size‐proportionate access to resource) to asymmetric (size‐disproportionate access to resources) as fertility and productivity increase. Our results emphasize the need to mitigate chronic human‐induced nutrient inputs to ecosystems in order to maintain and restore plant diversity and associated ecosystem functioning.